Socio-Economic Analysis of Agroforestry Systemand its Financial Efficiency Inmizoram, India - Zarzoliani; Lalnundanga; Lalriliana, F. (Indian Forester, 2017)
This study was conducted in selected agroforestry farms in Mizoram, India, to find out the outcome of socio-economic diagnosis as well as the financial efficiency of different agroforestry systems like mixed cropping, hedgerow farming, agrosilvopastoral and monocropping as control. Money spent and earned from each of the agroforestry systems were estimated as financial energy. Energy andmonetary flowswere represented by Megajoules per hectare per year (Mj ha-1 yr-1) and Rupees per hectare per year (` ha-1 yr-1 ) respectively. Human labour was the chief input system under study. The energy input through human is calculated on the basis of per hour energy expenditure by man using the standard values. The production, consumption and profit were estimated based on the data collected from the sites. Farm income was the main motives of agroforestry adoption followed by enhanced productivity of food crops. Management practices of different components were also recorded through questionnaire survey. The economic efficiency of each system under study was determined by calculating the monetary input: output ratio. All the land use systems showed significant results and positive economic return, which proved to be more favourable than the traditional jhum cultivation land use system. And finally, challenges faced by farmers were also addressed when adopting agroforestry system.